2015
DOI: 10.1002/bjs.9802
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs associated with abdominal aortic aneurysms and peripheral arterial disease

Abstract: In this study, circulating levels of let-7e, miR-15a, miR-196b and miR-411 were differentially expressed in men with an AAA compared with healthy controls, but also differentially expressed in men with PAD. Modulation of these miRNAs and their target genes may represent a new therapeutic pathway to affect the progression of AAA and atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…MiR‐24 is significantly decreased in both tissue and plasma of AAA patients and is inversely related to the size of the AAA 192. Recently, miR‐33a‐5p, let‐7i‐5, miR‐652‐3p and miR‐331‐3p are elevated in plasma of AAA patients compared with healthy controls, and miR‐192‐5p, miR‐10b‐5p, miR‐194‐5p, miR‐215‐5p, miR‐205‐5p, miR‐16‐5p, miR‐126, miR‐124a, miR‐155, miR‐223, miR‐29b, miR‐15a and miR‐15b are decreased 191, 193. However, miR‐29b was up‐regulated in human tissues from thoracic AA patients 187.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 98%
See 2 more Smart Citations
“…MiR‐24 is significantly decreased in both tissue and plasma of AAA patients and is inversely related to the size of the AAA 192. Recently, miR‐33a‐5p, let‐7i‐5, miR‐652‐3p and miR‐331‐3p are elevated in plasma of AAA patients compared with healthy controls, and miR‐192‐5p, miR‐10b‐5p, miR‐194‐5p, miR‐215‐5p, miR‐205‐5p, miR‐16‐5p, miR‐126, miR‐124a, miR‐155, miR‐223, miR‐29b, miR‐15a and miR‐15b are decreased 191, 193. However, miR‐29b was up‐regulated in human tissues from thoracic AA patients 187.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 98%
“…Additionally, the expression of miR‐146a is different in different types of samples from AAA patients. It is increased in AAA tissues 188 but is decreased in plasma of AAA patients 191. This may be because of different sources of sample and disease characteristics.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al identified increased expression of miR-191-3p, -455-3p, and -1281 in the whole blood of AAA patients compared to controls, while a separate study showed decreased expression of miR-126, -124a, -146a, -155, -223, -29b, -15a, and -15b in AAA [164, 165]. Stather et al reported reduced expression of let-7e, miR-15a, and -196b in the peripheral blood of AAA patients and increased expression of miR-411 as compared to controls [165]. The increased expression of some miRNA in AAA tissue and decreased expression in peripheral blood (i.e., miR-146a and miR-29b) demonstrate the complex nature of using miRNA as biomarkers of disease progression.…”
Section: Epigenetic Risk Factorsmentioning
confidence: 99%
“…71 Recently, many investigators have reported circulating micro-RNAs associated with AAA presence, such as miR-155, miR-191-3p, miR-455-3p, miR-1281, and miR-411. [72][73][74] Theoretical micro-RNAs have advantages over other circulating nucleic acids as markers in diagnostic tests because of their stability in blood samples. There have also been studies using lipidomics.…”
Section: Future Progress In Identifying Circulatingmentioning
confidence: 99%